A 360-Degree View of a Hospital by Analysing Patient's Online Reviews Using Fuzzy Sentiment Analysis. (September 2021) - Gour, Alekh; Kumari, Sony
Millions of people use Internet for developing new skills, booking online tickets, socialising, etc. Out of the sundry activities, giving online reviews by customers has become very customary these days and the fastest medium to make one's voice heard. With the advent of analytics, more specifically, text mining, the online reviews of the customers have made a huge difference in shaping the future strategies of the companies and have also helped them to study the customer responses of their rivals. In an effort to help hospitals analyse the patient's reviews present online on various social media platforms, this paper analyses the 659 reviews of people across the nation, on one of the best medical college and hospital of India, All India Institute of Medical Sciences, New Delhi. An attempt is made in this article to develop fuzzy sentiment analysis model with integration of naïve base classifier, which helps to analyse reviews of different hospitals and can come up with their own social media competitive analysis strategy. The results reveal the value text mining can bring to the table for any hospital and the immense business value that it holds.